Gibbs sampler approval to biomedical data problem analysis - Chin, Siew Hoo. (2008)
The modelling and analysis of missing medical data are done using the Bayesian Markov Chain Monte Carlo (MCMC) methods. WinBUGS, an interactive windows program for Bayesian analysis of complex statistical models using Markov Chain Monte Carlo (MCMC) techniques are applied to aid our understanding of applying Bayesian theory to evaluate missing medical data.